Design MIMO 1x8 Antenna for Future 5G Applications - Yusnita Rahayu; Muhammad Rifqy Asrul; Tulus Rahayu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper presented the design of MIMO 1x8 antenna operating at 38 GHz for future 5G applications. The antenna used the Rogers RT / duroid 5880 substrate with a thickness of 0.787 mm and a dielectric constant of 2.2. This antenna has 1x8 elements with 13.4 dBi of gain and the return loss of -15.76 dB. It has approximately 1.294 GHz bandwidth within the range of 37.485 GHz-38.779 GHz. The comparison performances between both antennas MIMO 1x4 and 1x8 are also discussed. It is shown that both radiation patterns are similar. The increasing number of elements affect to the gain and frequency. The proposed antenna meets the 5G requirements.